Financial Information Transparency and Data Security on Building User Trust in Peer-to-Peer Lending Platforms in Indonesia - Meiske Wenno; Muhamad Ammar Muhtadi; Rully Fildansyah (Westscience Press, 2026)
This study examines the influence of financial transparency and data security on user trust in peer-to-peer (P2P) lending platforms in Indonesia. The rapid growth of fintech services has increased public adoption of digital lending platforms; however, concerns regarding transparency and cybersecurity remain significant challenges affecting consumer confidence. This research employed a quantitative approach using a survey method involving 250 respondents who had experience using P2P lending platforms in Indonesia. Data were collected through structured questionnaires using a five-point Likert scale and analyzed using SPSS version 25. The results indicate that financial transparency has a positive and significant effect on user trust, demonstrating that clear and accessible financial information enhances perceptions of platform reliability and accountability. Data security was also found to positively and significantly influence user trust, indicating that strong protection of personal and financial information increases confidence in digital transactions. Simultaneously, financial transparency and data security significantly influence user trust in P2P lending services. The findings suggest that fintech companies should strengthen transparent financial communication and cybersecurity systems to maintain public trust and support the sustainable development of digital financial services in Indonesia.